1993
DOI: 10.1080/00221325.1993.9914747
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative and Proximal Influences on the Social Environment and Children's Creative Potential

Abstract: The influences of socioeconomic status (SES), maturation, school, and sex on creative potential were examined by administering the Torrance Tests of Creative Thinking to 1,445 children. Comparisons of means indicated that scores increased with SES, sixth-grade children scored slightly higher than fifth-grade children, and girls in general earned higher scores than boys. Additionally, the school setting and in particular the classroom atmosphere seemed to be far more important to creative potential than has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
1
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 39 publications
6
32
1
7
Order By: Relevance
“…Besides teachers' behaviors, the global climate of a particular school and the immediate atmosphere of a classroom decisively influence creative performance (Dudek, Strobel, & Runco, 1993). Such classroom atmosphere as providing opportunities for decision making, accepting varied perspectives, and enhancing students self-confidence surely contribute to creative thinking (Fleith, 2000).…”
Section: School and Technological Creativitymentioning
confidence: 99%
“…Besides teachers' behaviors, the global climate of a particular school and the immediate atmosphere of a classroom decisively influence creative performance (Dudek, Strobel, & Runco, 1993). Such classroom atmosphere as providing opportunities for decision making, accepting varied perspectives, and enhancing students self-confidence surely contribute to creative thinking (Fleith, 2000).…”
Section: School and Technological Creativitymentioning
confidence: 99%
“…As a favorable learning environment is critical to the development of students' creative potential, a number of studies have theoretically and empirically asserted a positive relationship between CLE and students' creativity (Amabile, 1996;Beghetto, 2005;Chambers, 1973;Cole et al, 1999;Dineen, 2006;Dineen & Niu, 2008;Dudek et al, 1993;Esquivel, 1995;Fryer, 2006;Gilbert et al, 2006;Hasirci & Demirkan, 2003;Hill & Amabile, 1993;Niu & Sternberg, 2003;Niu, 2003;Sak, 2004).…”
Section: Classroom Learning Environmentmentioning
confidence: 97%
“…Creativity needs to be nurtured from an early stage of life; however, giving individuals opportunities to develop their creativity at different learning stages is also required (Craft, 2006). A large number of researchers have perceived the significant effects of the learning environment on students' creative performance (Amabile, 1996;Beghetto, 2005;Chambers, 1973;Cole, Sugioka, & Yamagata-Lynch, 1999;Dineen, 2006;Dineen & Niu, 2008;Dudek, Strobel, & Runco, 1993;Esquivel, 1995;Fryer, 2006;Gilbert, Prenshaw, & Ivy, 2006;Hasirci & Demirkan, 2003;Hill & Amabile, 1993;Nin & Sternberg, 2003;Niu, 2003;Sak, 2004). In addition to the learning environment factors, motivation has also been identified as essential for individual creativity, and this may be the most straightforward issue to address in attempts to stimulate creativity (Amabile, 1983(Amabile, , 1996Hon, 2012;Sternberg & Lubart, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Dudek, Strobel, and Runco (1993) investigated the influence of school environment on the creative ability of fifth-and sixth-grade students from 11 schools in Montreal using Torrance Tests of Creative Thinking. Results indicated that the environment of a school, the social dynamics prevailing in a classroom and interaction between students and teachers have a clear impact on the growth of students' creative abilities.…”
Section: Theoretical Frameworkmentioning
confidence: 99%